JURNAL PENGARUH KUALITAS PELAYANAN DAN KINERJA PEGAWAI TERHADAP KEPUASAN MASYARAKAT PADA PELAYANAN KTP ELEKTRONIK DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN KARANGANYAR: PENGARUH KUALITAS PELAYANAN DAN KINERJA PEGAWAI TERHADAP KEPUASAN MASYARAKAT PADA PELAYANAN KTP ELEKTRONIK DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN KARANGANYAR - Eko Agus Santoso; Aris Tri Haryanto; Herning Suryo Sarjono (Master of Public Administration, Universitas Slamet Riyadi, 2022)
The development of service quality and community demands for quality services,currently there are still many complaints from the public in the e-KTP service atthe Population and Civil Registration Service in Karanganyar Regency. Thepurpose of this study was to determine the effect of service quality and employeeperformance partially and simultaneously on community satisfaction in theElectronic ID card service at the Population and Civil Registration Office ofKaranganyar Regency. This type of research is a quantitative approach. Theresearch sample is 100 community respondents who use e-KTP services. Datacollection techniques using questionnaires, documentation, and literature study.The hypothesis testing technique uses Multiple Regression Analysis, t test, F test,and the coefficient of determination (R2). Based on the results of research anddata analysis, this study can be concluded that the quality of service andperformance partially and simultaneously affect public satisfaction with theElectronic ID card service at the Population and Civil Registration Office ofKaranganyar Regency.Keywords: Service Quality, Performance, Public Satisfaction